Corrosive Injuries of the Upper Gastrointestinal Tract - Meena, Babu Lal; Narayan, Kumar Shwetanshu; Goyal, Gopal; Sultania, Surendar; Nijhawan, Sandeep (Journal of Digestive Endoscopy, 2017)
Corrosive injury of the upper gastrointestinal tract is a worldwide clinical problem, mostly occurring in children. Alkaline agents produce deeper injuries whereas acidic agents produce superficial injuries usually. Hoarseness, stridor, and respiratory distress indicate airway injury. Dysphagia, odynophagia, and drooling of saliva suggest esophageal injury whereas abdominal pain, nausea, and vomiting are indicative of stomach injury. X-rays should be done to rule out perforation. Endoscopy is usually recommended in the first 12–48 h although it is safe up to 96 h after caustic ingestion. Endoscopy should be performed with caution and gentle insufflation. Initial management includes getting intravenous access and replacement of fluids. Hyperemia and superficial ulcerations have excellent recovery while deeper injuries require total parenteral nutrition or feeding jejunostomy. Patients suspected of perforation should be subjected to laparotomy. Common complications after corrosive injury are esophageal stricture, gastric outlet obstruction, and development of esophageal and gastric carcinoma.
Keywords: Corrosive injury; esophageal perforation; esophageal stricture; upper gastrointestinal tract